Upaya Diplomasi Indonesia dalam Kasus Pembebasan Pekerja Migran Indonesia Terpidana Hukum Pancung di Arab Saudi: Periode 2014-2018 - Dhiajeng Cinthya Prativi; Shary Charlotte Henriette Pattipeilhy (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
The problem of death penalty that befell Indonesian migrant workers in Saudi Arabia reached dozens of migrant workers starting from 2014-2018. Indonesian government in this case has made efforts to releasing the migrant workers which have been entangled by this death penalty and these efforts are a form of diplomatic relations, diplomatic protection, and the embodiment of official diplomacy in the first track diplomacy. Therefore, this research intends to describe Indonesia’s diplomatic efforts in the process of releasing death penalty’s convicted migrant workers in Saudi Arabia, and to describe the Indonesian government’s inhibition in guarding cases that ensnare the migrant workers due to Indonesia’s lower bargaining position than Saudi Arabia. This research uses two concepts, first concept is diplomacy, that can explain the efforts of Indonesian government diplomacy, formal diplomacy or the informal diplomacy. Second concept is bargaining position which can explain the obstruction of the Indonesian government because of its bargaining position in overseeing the cases. The results of this research are Indonesia's bargaining position is lower and weaker compared to Saudi Arabia because of several factors such as poor governance of the protection of Indonesian migrant workers, Indonesia’s dependency on Saudi Arabia, Indonesia’s economic problems, and owning death penalty system in Indonesia.